Over-diuresis or cardiac tamponade? An unusual case of acute kidney injury and early closure. Issue 2 (1st January 2016) - Singh, Gurkeerat; Sabath, Bruce
Abstract : An 84-year-old man with hypertension and a history of deep venous thrombosis (on warfarin) was admitted with shortness of breath presumed to be due to congestive heart failure. Echocardiogram performed the following day showed a low-normal ejection fraction with signs of elevated right-sided pressures but was otherwise normal. He improved with diuretic therapy but after a few days was found to be hypotensive with a concomitant rise in creatinine with decreased urine output. This was felt to be secondary to over-diuresis but he did not respond to small boluses of intravenous fluids as his kidney function continued to worsen and hypotension persisted. He was transferred to the intermediate care unit where a rapid, bedside ultrasound revealed a new, moderate-sized pericardial effusion with tamponade physiology. Pericardiocentesis, with removal of 750 cc of frank blood, led to dramatic improvement in blood pressure, kidney function, and urine output. Here, we demonstrate the utility of point-of-care ultrasound in a community hospital setting where urgent echocardiogram is not routinely available. We also report acute kidney injury due to pericardial tamponade reversed with therapeutic pericardiocentesis.